Applying systems thinking and aligning it to systems engineering - Kasser, Joseph; Mackley, Tim (International Council on Systems Engineering, 2008)
This is a paper on thinking about thinking. Systems engineering is an emerging discipline in the area of defining and solving problems in the manner of (Wymore, 1993). The emerging paradigm for problem solving is “systems thinking”. Both systems engineering and systems thinking have recognized the need to view a system from more than one perspective. This paper proposes a set of perspectives for applying systems thinking in systems engineering and then defines a systems thinking perspective set of views for a system, the use of which will provide one way of aligning systems thinking to systems engineering. The paper then provides an example of applying the set of perspectives to the Royal Air Force Battle of Britain Air Defence System and shows that not only does the set of perspectives provide a way to model the system; it also picked up two potentially fatal flaws in the system. The paper then concludes with some observations on the state of systems engineering from a number of the perspectives.